Some Fixed Point Theorem for Mapping on Complete G-Metric Spaces. (15th September 2008) - Mustafa, Zead; Obiedat, Hamed; Awawdeh, Fadi
Abstract : We prove some fixed point results for mapping satisfying sufficient conditions on completeG -metric space, also we showed that if theG -metric space( X, G ) is symmetric, then the existence and uniqueness of these fixed point results follow from well-known theorems in usual metric space( X, d G ), where( X, d G ) is the usual metric space which defined from theG -metric space( X, G ) .